Dinamika Ekonomi di Lintasan Kereta Api Cirebon—Kadipaten pada Abad ke 19–20 M - Yanti, Rus; Dewangga Eka Mahardian; Iwan Hermawan; Jauharatna, Katrynada (Penerbit BRIN (BRIN Publishing), 2023)
Abstract. The Economic Dynamics along the Cirebon-Kadipaten Railway Route in the 19th–20th Centuries. The Dutch East Indies government built many facilities and infrastructures related to the economy. The railway line, which began construction in the 19th century, became one of the driving forces that transformed the Cirebon—Kadipaten region into bustling economic centres. Cirebon-Kadipaten is one of the ancient routes formerly traversed by trains from the Dutch company Semarang-Cheribon Stroomtram Maatschappij (SCS), leaving behind many archaeological traces. The SCS route also enlivened the economic centres along its western path, such as sugar factories and markets. The ebbs and flows of the economy along the western route and its impact on urban development remain unknown. Through literature reviews and field surveys, this paper identifies economic centres along the western SCS route and assesses the extent to which this route impacted urban development in an effort to reconstruct local history. The research results indicate active economic centres peaking in the early 20th century. Sharp economic fluctuations began occurring in the late 20th century due to economic decline, affecting the takeover of economic assets, decreased trading activities, and repurposing of economic buildings. This decline ultimately marked the end of the economic golden age along the western route (Kadipaten) coinciding with the demise of the railway line that supported it, and urban development entered a stagnant phase. These setbacks eventually marked the end of the economic golden age along the western route (Kadipaten) coinciding with the demise of the railway line that supported it, and urban development remained stagnant. However, there were tendencies towards eastern development again at the beginning of the millennium, reminiscent of the 19th century, characterized by bustling local markets, local artisans, and Pecinan shophouses. Keywords: Cirebon, Semarang Cheribon Stroomtram, Kadipaten, railway, economic centres Abstrak. Pemerintah Hindia Belanda membangun banyak sarana dan prasarana yang berkaitan dengan perekonomian. Jalur kereta api yang mulai dibangun pada abad ke-19 menjadi salah satu motor penggerak yang mengubah daerah Cirebon–Kadipaten menjadi kantung-kantung ekonomi yang tidak pernah sepi. Cirebon—Kadipaten merupakan salah satu jalur kuno yang dulu pernah dilintasi kereta api buatan perusahaan Belanda bernama Semarang-Cheribon Stroomtram Maatschappij (SCS) yang banyak meninggalkan bukti arkeologis. Lintasan SCS juga turut meramaikan kantung-kantung ekonomi yang dilaluinya di jalur barat, seperti pabrik gula dan pasar. Bagaimana pasang surut perekonomian di jalur barat dan dampaknya terhadap perkembangan kota, masih belum diketahui. Melalui studi pustaka dan survei lapangan, tulisan ini mengidentifikasi kantung-kantung ekonomi di sepanjang jalur barat SCS dan menakar sejauh mana jalur tersebut berdampak terhadap perkembangan kota sebagai upaya rekonstruksi sejarah lokal. Hasil penelitian menunjukkan kantung-kantung ekonomi aktif dan mencapai puncaknya pada awal abad ke-20. Fluktuasi ekonomi yang tajam mulai terjadi pada akhir abad ke-20 sebagai imbas dari kemunduran ekonomi (malaise) yang berdampak pada pengambilalihan aset ekonomi, penurunan aktivitas perdagangan, serta pengalihfungsian bangunan-bangunan ekonomi. Kemunduran tersebut pada akhirnya menandai berakhirnya masa keemasan perekonomian di jalur barat (Kadipaten) bersamaan dengan matinya jalur kereta api yang menghidupinya, dan perkembangan kota berada pada fase stagnan, tetapi ada kecenderungan pada awal millennium, perkembangan tersebut kembali ke arah timur, seperti pada abad ke-19, yang ditandai dengan berkembangnya keramaian di pasar-pasar lokal, pengrajin lokal, dan ruko-ruko di Pecinan. Kata kunci: Cirebon, Semarang Cirebon Stroomtram, Kadipaten, kereta api, kantung ekonomi